Evaluation of YouTubeTM as an Information Source for Indirect Restorations: Cross-Sectional Evaluation - Işıl Doğruer; Merve Kütük Ömeroğlu (European Annals of Dental Sciences)

(untitled)
Purpose: To evaluate the usefulness and quality of popular videos about indirect restorations shared by different uploaders onYouTube and to evaluate the demographic characteristics of the videos.Materials and Methods: The most commonly used terms related directly to indirect posterior restorations were determined as"inlay" and "onlay" in this topic. Of the 400 videos (200 for each topic), 40 videos were selected for analysis. Evaluations weremade for each video in terms of the following: (1) number of views, (2) number of comments, (3) days since up-load, (4) numberof ’likes’, (5) Viewing rate; [(number of views/number of days since upload) * 100%], (6) Viewer interaction, (7) Usefulness Indexscore, (8) 5-point global quality scale (GQS) criteria.Results: No statistically significant difference was found among usefulness scores and video sources. (p=0.754). Based on theusefulness score, 20% were classified as good, 40% as poor, and 40% as moderate. No statistically significant difference was foundamong primary purpose of videos and video sources. (p=0.754). The greatest number of videos (42.5%) was uploaded by dentists(n=17). When the primary purpose is evaluated for the videos uploaded by dentists, the highest numerical value was determined aseducation for health professionals (52.9%) (n=9).Conclusions: The contents of YouTube videos regarding the indications and production stages of inlay and onlay restorations needto be revised according to our evaluation criteria. The number of educational videos providing detailed content and information topatients should be increased.Keywords: Indirect restoration, Inlay, Onlay, Video analysis, YouTube